2014
DOI: 10.1111/and.12376
|View full text |Cite
|
Sign up to set email alerts
|

Body mass index, waist-to-hip ratio, waist circumference and waist-to-height ratio cannot predict male semen quality: a report of 1231 subfertile Chinese men

Abstract: There were controversial results between obesity-associated markers and semen quality. In this study, we investigated the correlations between age, obesity-associated markers including body mass index (BMI), waist-to-hip ratio (WHR), waist-to-height ratio (WHtR) and waist circumference (WC), the combination of age and obesity-associated markers, semen parameters and serum reproductive hormone levels in 1231 subfertile men. The results showed that BMI, WC, WHR and WHtR were positively related to age, and there … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 24 publications
2
39
0
3
Order By: Relevance
“…However, these results have not been replicated in all reports on the topic [1924]. Thus, we should be careful when interpreting the results, as they arise from cross-sectional studies or prospective population-based cohort studies on couples attempting to conceive, uncontrolled and non-randomized.…”
Section: Introductionmentioning
confidence: 96%
“…However, these results have not been replicated in all reports on the topic [1924]. Thus, we should be careful when interpreting the results, as they arise from cross-sectional studies or prospective population-based cohort studies on couples attempting to conceive, uncontrolled and non-randomized.…”
Section: Introductionmentioning
confidence: 96%
“…Clinical studies suggested a decreased testosterone level in serum in reproductive‐age men with diet‐induced obesity . However, the underlying mechanisms are still not obvious.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical studies suggested a decreased testosterone level in serum in reproductive-age men with diet-induced obesity. 31,32 However, the underlying mechanisms are still not obvious. The Leydig cells, which are located between the seminiferous tubules of the testis, are responsible for the synthesis and secretion of testosterone.…”
Section: Discussionmentioning
confidence: 99%
“…Тем не менее, результаты этих работ демонстрируют более низ-кую распространенность патозооспермии, а в одной из работ даже отрицается влияние ожирения на по-казатели сперматогенеза [15]. Это может быть связано с двумя факторами -отсутствием учета именно вис-церального ожирения (работы основаны на измерении ИМТ), а также особенностью нашей выборки паци-ентов.…”
Section: обсуждение основного результата исследованияunclassified